Arterial hypertension and cancer. Issue 10 (31st July 2013) - Milan, Alberto; Puglisi, Elisabetta; Ferrari, Laura; Bruno, Giulia; Losano, Isabel; Veglio, Franco
<x xml:space="preserve">Abstract</x> Arterial hypertension and cancer are two of the most important causes of mortality in the world; correlations between these two clinical entities are complex and various. Cancer therapy using old (e.g., mitotic spindle poisons) as well as new (e.g., monoclonal antibody) drugs may cause arterial hypertension through different mechanisms; sometimes the increase of blood pressure levels may be responsible for chemotherapy withdrawal. Among newer cancer therapies, drugs interacting with the VEGF (vascular endothelial growth factors) pathways are the most frequently involved in hypertension development. However, many retrospective studies have suggested a relationship between antihypertensive treatment and risk of cancer, raising vast public concern. The purposes of this brief review have then been to analyse the role of chemotherapy in the pathogenesis of hypertension, to summarize the general rules of arterial hypertension management in this field and finally to evaluate the effects of antihypertensive therapy on cancer disease.